The Jurisprudence of Religious Moderation: Strengthening Al-Wathanniyah Values at the Intersection of Islam and Nationality - Akil, Muhammad; Darmawangsa, Andi; Hasibuddin, M.; Ardi (Jurnal IUS Kajian Hukum dan Keadilan, 2024)
The purpose of this research is to analyze the concept of religious moderation fiqh and the value of al-wathanniyah at the intersection between Islam and nationalism in Indonesia as well as to formulate strategies and efforts that can be made to strengthen the value of al-wathanniyah as a basis in realizing religious moderation fiqh in Indonesia. This research uses qualitative research methods. Data collection techniques are carried out through in-depth literature studies on related classical and contemporary literature sources, as well as conceptual analysis to critically and comprehensively identify, explore, and map key concepts. The research results explain that the concept of religious moderation fiqh which emphasizes the attitude of tawassuth (moderate), tawazun (balanced), and i’tidal (straight) in understanding and practicing Islamic teachings has a meeting point with the value of al-wathanniyah or love for the homeland as part of the faith of a Muslim in Indonesia. Strengthening the value of al-wathanniyah or love for the homeland at the intersection between Islam and nationalism becomes the key to realizing the fiqh of religious moderation. These two concepts are in line with realizing a just, peaceful, prosperous society, and upholding unity in diversity in accordance with the ideals of the nation. To strengthen it as a basis for religious moderation in Indonesia, a comprehensive strategy is needed that includes aspects of education by integrating these values in the curriculum, spreading moderate discourse through various media, community empowerment, the role of the government in regulations by involving religious and community leaders, as well as cooperation and dialogue among stakeholders to build a collective understanding in the Indonesian context.